2019
DOI: 10.1177/1475921718820770
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the resonance frequency of buildings following strong seismic deformation as a proxy for structural health

Abstract: Elastic properties of civil engineering structures change when subjected to a dynamic excitation. The modal frequencies show a rapid decrease followed by a relaxation, or slow recovery, that is dependent on the level of damage. In this article, we analyze the slow recovery process applying three relaxation models to fit real earthquake data recorded in a Japanese building that shows variant structural state over 20 years. Despite the differences in conditions, the different scales and the complexity of a real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…This is analogous to the observations from Figure 1 and those reported by Johnson and Jia 10 and Guéguen et al, 12 and represents a distinctive signature of atypical nonlinearity (i.e., nonlinear elasticity) as observed in several materials 6,18 and building systems. 2 Moreover, for the same drift value, modulus softening diminishes progressively as loading increases, indicating that the structural response is not governed by the strain (drift ratio) amplitude. Figure 3 shows the effects of strain rate on the frequency variation during fast loading (i.e., co-seismic transient frequency drop, softening) and recovery (i.e., after loading), observed in the ANX building during earthquakes.…”
Section: Case 1: the Anx Buildingmentioning
confidence: 94%
See 2 more Smart Citations
“…This is analogous to the observations from Figure 1 and those reported by Johnson and Jia 10 and Guéguen et al, 12 and represents a distinctive signature of atypical nonlinearity (i.e., nonlinear elasticity) as observed in several materials 6,18 and building systems. 2 Moreover, for the same drift value, modulus softening diminishes progressively as loading increases, indicating that the structural response is not governed by the strain (drift ratio) amplitude. Figure 3 shows the effects of strain rate on the frequency variation during fast loading (i.e., co-seismic transient frequency drop, softening) and recovery (i.e., after loading), observed in the ANX building during earthquakes.…”
Section: Case 1: the Anx Buildingmentioning
confidence: 94%
“…Figure 3 shows the effects of strain rate on the frequency variation during fast loading (i.e., co-seismic transient frequency drop, softening) and recovery (i.e., after loading), observed in the ANX building during earthquakes. 2,16 The same Δ max ranges as in Figure 2 are considered. The responses to earthquakes occurring between 2006 and 2011 (i.e., before the 2011 Tohoku earthquake) and during 2012 (i.e., after the 2011 Tohoku earthquake) are considered, grouped, and averaged.…”
Section: Case 1: the Anx Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the ratio τ max / τ min computed from the relaxation function in Figure 3B 23 increased from ∼6 to ∼23 in the ANX building, and from ∼9 to ∼18 for THU. This ratio denotes the different time‐scale mechanisms that act in the time‐logarithmic segment of the recovery and characterizes the diversity of the crack sizes 14 (ie, preexistent and new ones). From this we can infer that after the 2011 event the variety of the cracks in the ANX and THU structures was quadrupled and doubled, respectively.…”
Section: Observations In Japanese Buildingsmentioning
confidence: 99%
“…Over the past three decades, scientific progress has mainly come from numerical and analytical models, although some pioneering instrumental observations have confirmed the role and origins of these rotations in seismic damage patterns. As stated by Trifunac et al [ 12 ] and recently confirmed by Astorga et al [ 13 , 14 , 15 ], significant progress in the understanding of the dynamics of buildings and the physics of the processes activated during earthquakes can only be achieved by generalising experimental recordings in more instrumented structures, in spite of the development of increasingly sophisticated numerical models. With regard to rotation, Lee and Trifunac [ 16 ] noted that despite recurrent engineering studies that have shown the importance of rotations in the response of buildings, the development and deployment of specific strong motion instruments to record rotations have remained somewhat rare.…”
Section: Introductionmentioning
confidence: 99%